(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
Practically all Romance languages have complement clitic pronouns which basically replace the arguments of a verb. Only a sub-area of Romance, extending from France through northern Italy to the Adriatic Sea, also has subject clitics, connected to the syntactic subject of an inflected verb. The subject clitics of northern Italy have been studied in depth, and the resulting picture shows strong variation. A series of absolute and implicational generalizations, though, tells us that the variation is within a single system. The Occitan varieties of Piedmont and Southern France at first sight seem to belong to the same system; they have just fewer forms of subject clitics than other northern Italian dialects, and generally these clitics are optional. On closer inspection, though, more radical differences appear to exist between Occitan and northern Italian, in this respect. While in northern Italian and northern Romance it is possible to recognise links between subject clitics and subject agreement, in Occitan most of the functions of these elements appear to have a pragmatic nature. The only exception is the 3rd sg. impersonal clitic, which is obligatory. This property violates in a very interesting way the generalizations made on NIDs and leads us to conclude that while northern Romance varieties can be seen as types of non-null subject languages, Occitan dialects represent particular kinds of null subject languages. KEYWORDS: clitics, pronouns, null subject, Occitan, Romance languages